SPIRITUAL DEVELOPMENT IN SUFISM: THE PATH TO PERSONAL PERFECTION AND MORAL GROWTH (Modern American Journal of Social Sciences and Humanities, 2025)
This article explores the foundational principles of spiritual and moral perfection, emphasizing the integral role of inner purification, ethical behavior, and heartfelt sincerity in human development. It examines traditional teachings from Sufism and Islamic scholarship that guide the believer toward achieving balanced spiritual maturity. The study highlights the relationship between the guidance of spiritual mentors (sheikhs) and the disciple’s personal efforts in overcoming vices and cultivating virtues. It also discusses how spiritual and moral growth contributes to overall human well-being and societal harmony. This work provides valuable insights into the enduring relevance of spiritual education in contemporary moral and ethical development.